Instructions for medical use of medicinal products as a tool for clinical and pharmaceutical decisions: current status and transformation in the context of harmonization with the European Union - O. V. Getalo; O. O. Saliy; O. O. Pokotylo; L. A. Fukleva (Farmatsevtychnyi zhurnal, 2026)
Instructions for medical use (IMU) serve as the main source of information for safe use by healthcare professionals and patients and accompany each registered drug. IMU combines the functions of documents for both the doctor and the patient, which necessitates the need to balance the scientific completeness of information and its accessibility for non-specialists. In European practice, information about a medicinal product is structured in the form of separate documents: a summary of product characteristics (Summary of Product Characteristics, SmPC), aimed at healthcare professionals, and a package leaflet (Package Leaflet, PL), intended for patients. The aim of the work was to analyze the current state of IMU of medicinal products as an integrated source of information in making informed clinical and pharmaceutical decisions and the transformation of the document in the context of integration into EU legislation. It was found that the IMU, SmPC and PL have a common information basis, but differ in structure, volume and target orientation, where the SmPC is the most complete source of information about the medicinal product for making clinical decisions by healthcare professionals. It was shown that pharmacovigilance plays a key role in the formation and u pdating of information in theSmPC, IMU and PL, but the key difference lies in the methods of reporting adverse reactions and the levels of detail of risks. It was proven that the IMU is a compromise tool that provides access to key information for different categories of users. At the same time, limitations in volume and the need to adapt information may lead to the loss of some of the detailed scientific data fully provided in the SmPC. Certain clinical decisions (availability of clinical data, pharmacokinetics/pharmacodynamics, adverse reactions, drug interactions) involve the analysis of the SmPC by the physician to choose the optimal drug. Pharmaceutical solutions (dosage form, storage conditions, packaging, administration devices, etc.) are strategic approaches of the manufacturer at the stages of development and registration of a medicinal product, which directly affect the content and structure of the IMU, SmPC, PL. The transformation of the IMU in the context of harmonization of Ukrainian l egislation with EUrequirements involves the replacement of the IMU with the SmPC and PL, the use of QRD templates, and the digitalization of information about medicinal products. Standardization of the PL structure, improved readability, and the introduction of modern text-processing technologies ensure the accessibility and comprehensibility of information and support the safe use of medicinal products by patients. The transformation of the IMU into the SmPC and PL contributes to improving the quality of information, the safety of pharmacotherapy, and the efficiency of clinical and pharmaceutical decision-making.